2017
DOI: 10.5005/jp-journals-10031-1192
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dental Anxiety Levels in Patients undergoing Endodontic Treatment

Abstract: Introduction Dental anxiety may be defined as a state of unpleasant feeling combined with an associated feeling of impending doom or danger from within than from without. Anxious patients are difficult to manage and tend to avoid treatment. Aim The aim of the study is to evaluate the level of dental anxiety among patients undergoing endodontic treatment. Materials and methods Consent form and a pro forma of questionnaire [Modified Dental Anxiety Scale (MDAS)] in three different languages were used. The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…Segura-Egea et al reported similar percentage for woman (47%). While male mean anticipated pain in current study 38.40 ± 29.71 (38%) found lower than Segura-Egea et al [19] and Martín-González et al [1,5,12,13,16] One explanation for this pattern may be that males continue to conceal their fears because of their orthodox gender position [5] or because of social standards that they more bear pain than females. [19] Current study found no correlation with mean anxiety and pain perception with gender which in line with the Kanegane et al [20] These results indicated that women had higher anticipated pain levels than did men, but women did not differ from men on anxiety and pain in RCT.…”
Section: Gendercontrasting
confidence: 53%
See 2 more Smart Citations
“…Segura-Egea et al reported similar percentage for woman (47%). While male mean anticipated pain in current study 38.40 ± 29.71 (38%) found lower than Segura-Egea et al [19] and Martín-González et al [1,5,12,13,16] One explanation for this pattern may be that males continue to conceal their fears because of their orthodox gender position [5] or because of social standards that they more bear pain than females. [19] Current study found no correlation with mean anxiety and pain perception with gender which in line with the Kanegane et al [20] These results indicated that women had higher anticipated pain levels than did men, but women did not differ from men on anxiety and pain in RCT.…”
Section: Gendercontrasting
confidence: 53%
“…[11] which not only poses a risk to the patient's oral health but also poses serious medical conditions such as septicemia, sinusitis, and osteomyelitis. [12] Despite technical advancements in dentistry, anxiety about dental care and the fear of dental pain remain widespread worldwide and are considered a major barrier to dental care. [12] Based on previously published data, educating patients about anticipated post-endodontic pain and prescribing medicines to manage it can increase patient trust in their dentists, raise pain thresholds and improve their attitude toward future dental care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation